Lemongrass oil as a renewable additive for enhancing the oxidation and thermal properties of calophyllum inophyllum biodiesel - Mohan Govindasamy; Manikandan Ezhumalai; Arunkumar Munimathan; Saurav Dixit; Subhav Singh; Ratchagaraja Dhairiyasamy (Results in Engineering)
This study investigates the use of lemongrass oil (Cymbopogon citratus) as an antioxidant additive Calophyllum inophyllum methyl ester (CIME) biodiesel to enhance its oxidation stability. This experimental study systematically evaluates the impact of lemongrass oil as an antioxidant additive in biodiesel, employing a range of analytical techniques to quantify its influence on oxidation stability, thermal stability, and engine performance parameters. Biodiesel, while a promising renewable energy source, suffers from oxidation instability, limiting its storage and performance. The investigation aims to evaluate the effect of lemongrass oil on key parameters such as induction period, peroxide value, acid number, viscosity, and thermal stability. CIME was blended with Diesel in a 20:80 ratio (B20), and lemongrass oil was added in varying concentrations (5, 10, 15, and 20 ml per liter of biodiesel blend). The addition of lemongrass oil improved the induction period of B20 from 6 hours to 9.6 hours (B20LG20), reduced the peroxide value by 51 %, and limited acid number growth by 42 %. TGA results showed an increase in residual weight at 500 °C from 5 % for B20 to 15 % for B20LG20. Engine tests revealed a peak brake thermal efficiency of 31.2 % for B20LG20, slightly lower than Diesel (32 %). However, B20LG20 reduced CO and smoke emissions by 15 % and 25 %, respectively, while NO emissions were reduced by 6 % compared to B20. Lemon grass have significantly improved the stability and environmental performance of biodiesel blends, making it a viable additive for cleaner and more sustainable energy applications.